2019
DOI: 10.1186/s12906-019-2600-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated flavonoid-enriched fraction from Maclura tinctoria shows biological activity against Staphylococcus aureus and protects Galleria mellonella larvae from bacterial infection

Abstract: Background The Atlantic Forest biome extends along the entire Brazilian coast and is home to approximately 20,000 plant species, many of which are endemic; it is considered one of the hotspot regions of the planet. Several of these species are sources of natural products with biological activities that are still unknown. In this study, we evaluated the antimicrobial activity of 90 extracts derived from native Atlantic Forest tree species against Staphylococcus aureus , a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…This coincides with those reported in the literature, where prenylated flavanones show better activity than flavones [ 28 , 29 ]. The position of the hydroxyl substituents, as well as that of the prenyl group, appears to be important in the inhibitory activity of bacterial growth, observing that derivatives with OH at positions C-5, 7, and 4′ show better inhibitory activity, as well as the presence of prenyl groups in the C6 and C8 positions of Ring A, as previously reported [ 30 , 31 , 32 ]. Araya–Coultier et al (2018) showed that the position of the prenyl group affects the antimicrobial activity of flavonoids, when comparing the effect of lupiwighteone (5,7,4′-trihydroxy-8-prenylisoflavone) and wighteone (5,7,4′-trihydroxy-6-prenylisoflavone), on the Gram-positive strain L. monocytogenes .…”
Section: Resultssupporting
confidence: 76%
“…This coincides with those reported in the literature, where prenylated flavanones show better activity than flavones [ 28 , 29 ]. The position of the hydroxyl substituents, as well as that of the prenyl group, appears to be important in the inhibitory activity of bacterial growth, observing that derivatives with OH at positions C-5, 7, and 4′ show better inhibitory activity, as well as the presence of prenyl groups in the C6 and C8 positions of Ring A, as previously reported [ 30 , 31 , 32 ]. Araya–Coultier et al (2018) showed that the position of the prenyl group affects the antimicrobial activity of flavonoids, when comparing the effect of lupiwighteone (5,7,4′-trihydroxy-8-prenylisoflavone) and wighteone (5,7,4′-trihydroxy-6-prenylisoflavone), on the Gram-positive strain L. monocytogenes .…”
Section: Resultssupporting
confidence: 76%
“…It is the aim of the BIOPROS group that has been implemented a large-scale project to produce and test extracts from the Atlantic Forest trees, where species are still rarely studied for their biological activity. The BIOPROS Extract Library is also screened in other biological targets such as antibacterial [24,25] , Anticholinesterase inhibitor [26] , Insecticidal [27] , and phytonematode control [28] .…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have reported cytosolic presence and activity of diprenylated (iso)flavonoids ( 13 , 14 ). das Chagas Almeida et al ( 15 ) demonstrated that the antimicrobial activity of a plant extract rich in mono- and diprenylated (iso)flav(an)ones was exerted without permeabilization of the PM of Staphylococcus aureus (assessed through crystal violet uptake at extract concentrations up to 8× MIC) or any disruption of the cell surface (as evidenced by atomic force microscopy at the MIC), suggesting alternative targets in bacteria.…”
Section: Introductionmentioning
confidence: 99%